2011
DOI: 10.1111/j.1365-2605.2010.01053.x
|View full text |Cite
|
Sign up to set email alerts
|

Complex transcriptional control of the AZFa gene DDX3Y in human testis

Abstract: The human DEAD-box Y (DBY) RNA helicase (aka DDX3Y) gene is thought to be the major azoospermia factor a (AZFa) gene in proximal Yq11. Men with its deletion display no somatic pathologies, but suffer from complete absence of germ cells. Accordingly, DDX3Y protein is expressed only in the germline in spermatogonia, although the transcripts were found in many tissues. Here, we show the complex transcriptional control of a testis-specific DDX3Y transcript class with initiation at different sites upstream of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
58
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(61 citation statements)
references
References 51 publications
2
58
0
Order By: Relevance
“…49 In a recent study it has been reported that the human DBY RNA helicase gene is the major azoospermia factor a (AZFa) gene. 50 Men with its deletion display no somatic pathologies, but suffer from complete absence of germ cells. 50 Accordingly, DDX3Y protein is expressed only …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…49 In a recent study it has been reported that the human DBY RNA helicase gene is the major azoospermia factor a (AZFa) gene. 50 Men with its deletion display no somatic pathologies, but suffer from complete absence of germ cells. 50 Accordingly, DDX3Y protein is expressed only …”
mentioning
confidence: 99%
“…50 Men with its deletion display no somatic pathologies, but suffer from complete absence of germ cells. 50 Accordingly, DDX3Y protein is expressed only …”
mentioning
confidence: 99%
“…Both proteins are expressed in the testes; however, DDX3Y is found predominantly at premeiotic stages in spermatogonial cells, whereas DDX3X is detected later in spermatids (15,16,20). This divergent expression pattern arises due to complex transcriptional and translational control mechanisms (21,22) and it seems to predetermine presumed specific functions of DDX3Y in premeiotic spermatogenesis steps. Testis-specific DDX3Y transcription initiates from a distal promoter that takes place within upstream Y-specific minisatellite MSY2 repeats (21).…”
Section: Discussionmentioning
confidence: 99%
“…Testis-specific DDX3Y transcription initiates from a distal promoter that takes place within upstream Y-specific minisatellite MSY2 repeats (21). This distal promoter region for DDX3Y on the Y chromosome appears to be conserved in primates; however, it is not active upstream of the mouse Ddx3y genе (21). It has been shown that mouse homologue Ddx3y is expressed widely in all analyzed tissues (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation